A functional approach to compiling a specialized English-Slovene dictionary of green energy terms - Mrhar, Laura (ELOPE (Ljubljana), 2013)
The functional approach to lexicography argues that dictionaries must provide their users with concrete types of information, presented in a manner that suits their needs. To achieve this, the process of compiling specialized dictionaries must be improved. This paper examines the revision of a specialized English-Slovene Dictionary of Green Energy Terms, with particular emphasis on the functional approach to building specialized dictionaries. As the potential users of the unrevised dictionary differ from those of the revised version, this paper aims to show how the profile of the intended user affects the structure of the actual dictionary entry, as well as the dictionary's main functions. The main objective of the paper is therefore to put forward a sound theoretical foundation for the improved construction of LSP dictionaries, so that they will truly serve as a helpful tool in solving those problems that normally occur in LSP communication.
Keywords: funkcijska teorija; komunikacijske funkcije; mikrostruktura; profil uporabnika; slovarji; specializirana leksikografija